From: Geïllustreerd Zondagsblad van het Volksdagblad, 18-11-1906, p. 110. Slaves on their way to San-Thomé and Principe
From: Geïllustreerd Zondagsblad van het Volksdagblad, 18-11-1906, p. 110. Slaves on their way to San-Thomé and Principe.